The Relationship Between the Polymorphisms of RANK Gene and Type 2 Diabetes Mellitus in Postmenopausal Women. - Li, Jun; Sun, Chuanbing; Li, Siyuan; An, Xueyuan; Li, Ya; Shen, Yujuan; Tian, Hangning (Clinical Medicine Insights: Endocrinology & Diabetes, 2026)
Background: Studies have indicated an association between the receptor activator of nuclear factor-κB (RANK) gene and the pathogenesis of type 2 diabetes mellitus (T2DM). This study aimed to investigate the relationship between the polymorphisms at the RANK gene loci (rs3018362 and rs78326403) and T2DM in postmenopausal women from Xinjiang, China. Methods: This study enrolled 200 postmenopausal Han Chinese women who attended the First Affiliated Hospital of Shihezi University from October 2024 to March 2025. The research subjects were divided into two groups based on their medical history and results of the oral glucose tolerance test (OGTT): normal glucose tolerance group (NGT group, n = 95) and type 2 diabetes mellitus group (T2DM group, n = 105). Baseline data and biochemical indicators of the research subjects were collected and recorded. The polymorphisms of RANK gene loci were determined by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Results: 1) After correction for multiple testing using the Benjamini-Hochberg method, the levels of FPG, HbA1c, HDL, and TyG index were significantly higher in the T2DM group compared with the NGT group. 2) At the rs3018362 locus, there were statistically significant differences in the genotypic and allelic frequencies between the two groups. 3) Following Benjamini-Hochberg multiple testing correction, at the rs78326403 locus, compared with the major homozygous genotype (AA), carriers of the minor allele (TT + AT) in the NGT group had significantly lower levels of TG, LDL, TG/HDL ratio, and TyG index. 4) Binary logistic regression analysis revealed that HbA1c and the rs3018362 genotype were independently and statistically associated with T2DM. Conclusion: The polymorphism at the rs3018362 locus of the RANK gene may be related to T2DM in postmenopausal women from Xinjiang, China. Additionally, the polymorphism at the rs78326403 locus may be involved in glucose and lipid metabolism. Plain Language Summary: Why was this study done? Type 2 diabetes mellitus (T2DM) is one of the major public health issues worldwide, and its pathogenesis remains unclear. For women after menopause, hormonal changes may increase their risk of developing T2DM. Recent studies have suggested that the OPG-RANKL-RANK signaling pathway exerts a potential impact on T2DM. However, how exactly this pathway works in T2DM is still unclear. Therefore, this study aims to investigate the relationship between the polymorphisms at the RANK gene loci (rs3018362 and rs78326403) and T2DM in postmenopausal women. What did the researchers do? This study enrolled 200 postmenopausal Han Chinese women who were categorized into two groups. Baseline data of the participants were collected, relevant biochemical indicators were measured, the polymorphisms of RANK gene loci were determined, and subsequent statistical analysis were conducted. What did the researchers find? Our findings revealed that the polymorphism at the rs3018362 locus of the RANK gene may be associated with T2DM in postmenopausal women from Xinjiang, China. What do the findings mean? From a genetic perspective, this study investigated the correlations between the RANK gene loci polymorphisms and T2DM, as well as glycemic and lipid metabolic indicators, in postmenopausal women. The results lay a preliminary foundation for future basic and clinical research on the RANK gene.